Why Can't US Airlines Make Money? - Borenstein, Severin (American Economic Review, 2011)
US airlines have lost nearly $60 billion ($2009) in domestic markets since the 1978 deregulation, most of it in the last decade. The dismal financial record challenges the economics of deregulation. I examine some of the common explanations among industry participants and researchers—including high taxes and fuel costs, weak demand, and competition from lower-cost airlines. Major drivers seem to be the demand downturn after 9/11—demand remains much weaker today than in 2000—and the large cost differential between legacy and low-cost carriers, which has persisted even as the price differential between them has greatly declined.